GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 7, 1986 - NISHIO, Fumihiko; OHMAE, Hirokazu; OSADA, Kazuo (National Institute of Polar Research, 1988)
P(論文) departmental bulletin paper